2016
DOI: 10.1007/s00393-016-0236-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of methotrexate chronotherapy in collagen-induced rheumatoid arthritis in rats

Abstract: AimTo explore the circadian rhythm of serum interleukin (IL)-6 in collagen-induced arthritis (CIA) rats and compare the safety and effectiveness of methotrexate (MTX) administered traditionally and via chronotherapy.MethodsCIA rat models were immunized with bovine type II collagen. Serum IL-6 levels in normal and CIA rats were measured at 2, 6, 10, 14, 18, or 22 h after the light was turned on (HALO). MTX was administered to 6 HALO/18 HALO experimental groups of Wistar rats once daily according to the IL-6 rhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…IL-6 and other pro-inflammatory cytokines stimulate the synthesis of such ideal indicator in the hepatic cells [39,40] . Although MTX chronotherapy effectively lowered CPR and tumour necrosis factor-α (TNF-α) in rats with collagen induced-arthritis [41] , the highest level of CPR in the present study was in the MTX group. In harmony with our results, CRP and TNF-α were expressed immunohistochemically in the tubular epithelium of MTX-treated rats kidney [13] .…”
Section: Discussioncontrasting
confidence: 70%
“…IL-6 and other pro-inflammatory cytokines stimulate the synthesis of such ideal indicator in the hepatic cells [39,40] . Although MTX chronotherapy effectively lowered CPR and tumour necrosis factor-α (TNF-α) in rats with collagen induced-arthritis [41] , the highest level of CPR in the present study was in the MTX group. In harmony with our results, CRP and TNF-α were expressed immunohistochemically in the tubular epithelium of MTX-treated rats kidney [13] .…”
Section: Discussioncontrasting
confidence: 70%
“…Therefore, in vitro experimental results might not be consistent with those of in vivo experiments. Recent studies have revealed that the adrenal gland is often neglected in regulatory endocrine disruption screening and testing, even though it is the organ of the endocrine system that is most commonly the target of toxicity. The TP‐treated female rats showed a reduced mean ZF and an increased mean ZR compared with the respective control rats.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6, an important pro-inflammatory cytokine expressed in rheumatoid arthritis (OA) [ 30 ], mediates osteoclast activation, thus contributing to cartilage and bone breakdown and joint destruction. Previous studies have found that plasma IL-6 levels in rats with collagen-induced arthritis (CIA) were higher at almost every sampling time compared to those in normal rats, and IL-6 expression showed significant circadian rhythms, indicating higher levels during the light phase and lower levels during the dark phase [ 31 ]. Recent studies revealed a relationship between circadian rhythm and osteogenesis and osteoclastogenesis.…”
Section: Circadian Rhythm In Bonementioning
confidence: 99%